Achieving superior mechanical and magnetic properties in non-oriented electrical steel with high coherent nanoprecipitation - F. Fang; D. W. Hou; S. F. Dai; Y. X. Zhang; Y. Wang; L. L. Li; X. M. Zhang; G. Yuan; G. D. Wang (Materials Research Letters)
Non-oriented electrical steel strengthened by NiAl–Cu coprecipitates was successfully processed based on strip casting. Equiaxed grains of ∼ 37 µm with strong {411}〈148〉 texture were obtained after annealing. At the aging peak, a high density of nano-coprecipitates with a mean radius of ∼2.8 nm and low lattice misfit of ∼0.66% was formed and exhibited a core–shell structure consisting of a Cu-rich core and a NiAl shell, effectively reducing interface energy and retarding coarsening. Superior mechanical properties with an ultra-high yield strength of 952.4 MPa, magnetic properties with magnetic induction B50 of 1.677 T and iron loss P10/400 of 22.8 W/kg were achieved.